Effect of real earnings management on tax planning of listed manufacturing firms in Nigeria - Ado, Rabiu; Tanko, Udisifan Michael (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study examines the effect of real earnings management on corporate tax planning of listed manufacturing firms in Nigeria. Method: The study used secondary data of 41 listed manufacturing firms in Nigeria extracted from the annual reports and accounts of the sampled firms for the period 2012 to 2022. The data collected for the study were statistically analyzed using dynamic panel data from the generalized moment method (GMM). Results: The study found that abnormal production has positive and significant effect on tax planning, the study also revealed that abnormal discretionary expense has positive and significant effect on tax planning. The study also documents a positive and significant influence of abnormal production on tax planning. The study also reveals that real earnings management has a positive and significant impact on tax planning. Limitations: The study is limited to real earnings management and tax planning; it is limited to 41 listed manufacturing firms in Nigeria and covers  12 years,  from 2012 to 2022.   Contribution:  This study contributes to the existing literature by providing empirical evidence on the relationship between real earnings management and tax planning, specifically within the context of Nigerian manufacturing firms. The findings will inform policymakers and regulatory bodies regarding the effectiveness of current tax regulations and practices in Nigeria's manufacturing sector. Novelty: This study's focus on Nigerian manufacturing firms adds a novel dimension to the existing literature, as there may be unique factors and challenges specific to this context. In addition, the study provides a novel approach by employing dynamic panel data of GMM.